Company Performance Measurement Analysis PT. Romi Violeta Sidoarjo Using Malcolm Baldrige Criteria for Performance Excellence - Elvina Sinta Dewi; Didi Samanhudi (Budapest International Research and Critics University, 2022)
This research aims to assess the level of company performance using the Malcolm Baldrige Criteria for Performance Excellence with software SPSSRomi Violeta Sidoarjo, a rattan and wood furniture company, specializing in wicker and wood garden furniture. Performance measurement based on financial aspects alone causes the company not to know specifically what factors cause the company's performance to decline. The results of this study are the company's performance position is in the Emerging Industry Leader with a score of 627.01 and based on the recapitulation of the assessment of each variable it can be seen that in the company's employee performance the highest value is in the category of human resource focus, which is 78.37% which means the company always maintains good relations with employees, while the lowest value is in the business results category, which is 56.29%, which means that it still has to pay attention to matters relating to the development of organizational capabilities and its renewal of the main business environment. The results of this study are expected to be considered by the leadership regarding evaluating the performance of company employees to be in an excellent condition.